2023
DOI: 10.1177/10812865221137286
|View full text |Cite
|
Sign up to set email alerts
|

Modeling a labyrinthine acoustic metamaterial through an inertia-augmented relaxed micromorphic approach

Abstract: We present an inertia-augmented relaxed micromorphic model that enriches the relaxed micromorphic model previously introduced by the authors via a term Curl [Formula: see text] in the kinetic energy density. This enriched model allows us to obtain a good overall fitting of the dispersion curves while introducing the new possibility of describing modes with negative group velocity that are known to trigger negative refraction effects. The inertia-augmented model also allows for more freedom on the values of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The kinetic energy K and strain energy W of the reduced relaxed micromorphic model are shown in equations ( 1)-( 2) [43,109,112,135]:…”
Section: Bulk Equations and "Free Interface" Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic energy K and strain energy W of the reduced relaxed micromorphic model are shown in equations ( 1)-( 2) [43,109,112,135]:…”
Section: Bulk Equations and "Free Interface" Boundary Conditionsmentioning
confidence: 99%
“…It has been largely shown that the bulk mechanical response of mechanical metamaterials can be effectively explored using an elastic-and inertia-augmented micromorphic model (reduced relaxed micromorphic model) which is able to describe the main metamaterials' fingerprint characteristics (anisotropy, dispersion, band-gaps, size-effects, etc. ), while keeping a reduced structure (free of unnecessary parameters) [3,43,44,83,100,101,102,109,112,113,114,115,135]. This model can be linked a posteriori to real metamaterials' microstructures via an inverse fitting procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The relaxed micromorphic is a new generalized continuum model that allows to describe size-effects and band-gaps appearing in metamaterials (Rizzi et al, 2021a;Voss et al, 2023;Rizzi et al, 2022a,c;Ramirez et al, 2023;Demore et al, 2022;Rizzi et al, 2022d;Madeo et al, 2015) (in its dynamic setting). The relaxed micromorphic model belongs to the family of micromorphic models (Mindlin, 1964;Eringen, 1999) where the kinematics are given by the classical displacement 𝑢 ∶ 𝛺 → R 3 and the non-symmetric micro-distortion 𝑃 ∶ 𝛺 → R 3×3 .…”
Section: Introductionmentioning
confidence: 99%
“…The above mentioned advantages have led to a multitude of investigations in short-time from the numerical side (Sky et al, 2024(Sky et al, , 2021(Sky et al, , 2022bSchröder et al, 2022;Sarhil et al, 2023), from the modelling side (Rizzi et al, 2021a;Voss et al, 2023;Rizzi et al, 2022a,c;Ramirez et al, 2023;Demore et al, 2022;Rizzi et al, 2022d;Madeo et al, 2015), analytical solutions (Rizzi et al, 2022b(Rizzi et al, , 2021d, regularity of solutions (Knees et al, 2023b,a), and many others.…”
Section: Introductionmentioning
confidence: 99%
“…The band gap region is broad since the unit cell's design mostly exploits the Bragg-scattering mechanism. This unit cell is an optimized version of the cell presented in Voss et al [24], such that it was stable enough to be manufactured and mechanically loaded. The thickness of the beams was set equal to the thickness of the air gap throughout the unit cell and the number of air gaps in the radial direction was reduced.…”
Section: Introductionmentioning
confidence: 99%